PENGARUH PERENCANAAN PAJAK, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SEKTOR PERINDUSTRIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2023 - Tiara Anggini; Dani Sopian (Politeknik Negeri Ambon, 2025)
Introduction: This study investigates the impact of tax planning, profitability, and company size on earnings management in industrial sector companies listed on the Indonesia Stock Exchange between 2019 and 2023. Methods: The population for this research included all industrial sector companies listed on the IDX during the specified period. A purposive sampling method was employed, resulting in a sample of 24 companies with a five-year observation period, yielding 120 data points. The data analysis was conducted using multiple linear regression analysis with SPSS version 26 software. Results: The findings indicated that, when examined together, tax planning, profitability, and company size significantly affected earnings management. However, when analyzed individually, tax planning positively influenced earnings management, but this effect was insignificant. Profitability showed a negative but insignificant effect, while company size had a negative and significant impact on earnings management. Keywords: Tax Planning, Profitability, Company Size, Earnings Management.